Georhizobium profundi gen. nov., sp. nov., a piezotolerant bacterium isolated from a deep-sea sediment sample of the New Britain Trench. Issue 1 (3rd February 2020) - Cao, Junwei; Wei, Yuli; Lai, Qiliang; Wu, Yunjie; Deng, Junhao; Li, Jianyang; Liu, Rulong; Wang, Li; Fang, Jiasong
Abstract : A novel alphaproteobacterium, strain WS11 T, was isolated from a deep-sea sediment sample collected from the New Britain Trench. The full-length 16S rRNA gene of strain WS11 T had the highest sequence similarity of 97.6 % to Rhizobium subbaraonis JC85 T, followed by Mycoplana ramosa DSM 7292 T (96.9 %) and Rhizobium azooxidifex Po 20/26 T (96.8 %). Phylogenetic analysis of concatenated 16S rRNA, atpD and recA gene sequences showed that strain WS11 T was deeply separated from the species within the family Rhizobiaceae . Phylogenomic analysis based on the whole-genome protein sequences showed that strain WS11 T formed an independent monophyletic branch in the family Rhizobiaceae, paralleled with the species in the families Brucellaceae and Phyllobacteriaceae within the order Rhizobial es. Cells were Gram-stain-negative, oxidase- and catalase-positive, and aerobic short rods (1.5–2.4×0.9–1.0 µm). Growth was observed at salinities ranging from 0 to 5% (optimum, 1 %), from pH 6.5 to 9 (optimum, pH 7) and at temperatures between 20 and 30 °C (optimum, 28 °C). Strain WS11 T was piezotolerant, growing optimally at 0.1 MPa (range 0.1–70 MPa). The main fatty acid was summed feature 8 (C18 : 1 ω 7 c /C18 : 1 ω 6c ). The sole respiratory quinone was ubiquinone-10 (Q-10). The predominant polar lipids were phosphatidylcholine, two unidentified aminophospholipids and an unidentified phospholipid. The genome size was about 4.36 Mbp and the G+C content was 62.3 mol%. The combined genotypic and phenotypic data show that strain WS11 T represents a novel species of a novel genus in the family Rhizobiaceae, for which the name Georhizobium profundi gen. nov., sp. nov. is proposed (type strain WS11 T =MCCC 1K03498 T =KCTC 62439 T ).